Dichotic Hearing in Elderly Hearing Aid Users Who Choose to Use a Single-Ear Device - Ribas, Angela; Mafra, Nicoli; Marques, Jair; Mottecy, Carla; Silvestre, Renata; Kozlowski, Lorena (International Archives of Otorhinolaryngology, 2014)
Introduction Elderly individuals with bilateral hearing loss often do not use hearing aids in both ears. Because of this, dichotic tests to assess hearing in this group may help identify peculiar degenerative processes of aging and hearing aid selection.Objective To evaluate dichotic hearing for a group of elderly hearing aid users who did not adapt to using binaural devices and to verify the correlation between ear dominance and the side chosen to use the device.Methods A cross-sectional descriptive study involving 30 subjects from 60 to 81 years old, of both genders, with an indication for bilateral hearing aids for over 6 months, but using only a single device. Medical history, pure tone audiometry, and dichotic listening tests were all completed.Results All subjects (100%) of the sample failed the dichotic digit test; 94% of the sample preferred to use the device in one ear because bilateral use bothered them and affected speech understanding. In 6%, the concern was aesthetics. In the dichotic digit test, there was significant predominance of the right ear over the left, and there was a significant correlation between the dominant side with the ear chosen by the participant for use of the hearing aid.Conclusion In elderly subjects with bilateral hearing loss who have chosen to use only one hearing aid, there is dominance of the right ear over the left in dichotic listening tasks. There is a correlation between the dominant ear and the ear chosen for hearing aid fitting.
Keywords: hearing aids; auditory perception; aged; deafness; hearing